Advances and challenges of using CRISPR-Cas9 gene editing for treating Duchenne muscular dystrophy. Issue 1 (2017) - Ouellet, Dominique L; Duchêne, Benjamin; Iyombe-Engembe, Jean-Paul; Tremblay, Jacques P
No abstract available